ANALYSIS OF TREASURER ACCEPTANCE TO ACCRUAL BASE IMPLEMENTATION BASED ON GOVERNMENT REGULATION NO. 71 YEAR 2010: CASE STUDY IN OPEN UNIVERSITY - Olivia Idrus; Noorina Hartati (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
For determining the total income amount and load precisely in the same period, there are two available choices which are able to be the recording basis by accountants which are the cash basis and accrual basis. A study result implemented by the IFAC Public Sector Committee (2002) stated that accrual based reporting is useful in evaluating government performance related with costs of service, efficiency, and reaching goals. With accrual based reporting, users are able to identify the government’s financial position and its change, how the government funds its activities corresponding with the funding ability, so the real government capacity is able to be measured, In 2010, the accrual based Government Accounting Standard has finished being arranged by the Government Accounting Standard Committee and determined as a Government Regulation in Government Regulation Number 71 Year 2010. The implementations of the regulation are, Financial Reports of Central and Regional Governments are gradually motivated for applying accrual based accounting. The Open University as a Public University is not excluded from the Government Regulation Number 71 Year 2010. The transition of the recording method from the cash basis to the accrual basis of course will impact several matters. Because of that the researcher is interested for observing the acceptance attitude of treasurers in the Open University environment, in the Central Open University and the Long Distance Learning Program Unit-Open University which disperse in 39 Long Distance Learning Program Units-Open University, as a cause of the accounting basis transition. This acceptance attitude will observe the following aspects: Personal Comfort, Change as a Challenge, Employment Uncertainty, Job Results, Control of Employment, Freedom in Employment, and Satisfaction.Keywords: Acceptance Attitude, Change as Challenge, Control of Employment, Job Results, Personal Comfort, Satisfaction